EFFORTS TO IMPROVE EMPLOYEE PERFORMANCE THROUGH COMPENSATION POLICY AND JOB DESIGN EFFECTIVENESS MEDIATED BY JOB SATISFACTION AT MANDIRI UTAMA FINANCE SERANG BRANCH - Henny Ratnasari; Agus David Rahmansyah (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
This study aims to determine the relationship between compensation policy variables and the effectiveness of job design in improving employee performance and job satisfaction in mediating compensation policies and the effectiveness of job design in improving employee performance. Building a model of business phenomena and research gaps in improving employee performance at the Serang Branch of Mandiri Utama Finance with a purposive sampling technique. Data analysis using the SEM-PLS method. The results of the study show 1) Steering policies have a positive and significant effect on job satisfaction, 2) Job design effectiveness has a positive and significant effect on job satisfaction, 3) compensation policies have a positive and insignificant effect on employee performance, 4) Job design effectiveness has a positive influence and significant to employee performance, 5) Job satisfaction has a positive and significant impact on employee performance. 6) Job satisfaction mediates the effect of compensation policy significantly on employee performance, 7) Job satisfaction mediates the effect of job design effectiveness significantly on employee performance.